Acute pulmonary embolism caused by highly aggregated intravenous immunoglobulin. Issue 1 (21st July 2015) - Yu, C. F.; Hou, J. F.; Shen, L. Z.; Gao, K.; Rao, C. M.; Yang, P. Y.; Fu, Z. H.; Wang, Q. Z.; Li, Y. H.; Wang, L.; Liu, F.; Zhang, L.; et al.
Abstract : Background and Objectives: Six patients died and one patient survived following infusion of a specific lot of intravenous immunoglobulin (IVIG) within half an hour in May 2008. This study elucidated the underlying pathogenesis. Materials and Methods: A variety of protein fractionation and identification approaches were employed to determine the abnormal components in IVIG products obtained from the hospital where the patients were treated. Animal studies using mice and monkeys were conducted to elucidate the pathophysiological mechanisms. In animal experiments, the effect and distribution of immunoglobulin was investigated using HE staining and immunohistochemistry (IHC) separately, while platelets and fibrinogen depletion were utilized to determine a possible link between thromboembolism formation in animals and the lethal effect of the IVIG. The size and distribution of the protein aggregates were determined with Coulter Counter Multisizer‐3 after the dilution of the IVIG with plasma, and the lethal effect of the protein aggregates was simulated with artificial microparticles. Results: The IVIG retrieved from the hospital was found to have striking similarities to the heat‐treated IVIG in terms of protein aggregation profiles and lethal effects. Post‐mortem examination indicated that immunoglobulin aggregates were mainly found in the lung of the animals, while depletion of platelets and fibrinogen from the IVIG preparations failed to prevent the death of the animals. Similar amount of artificial microparticles caused animal death in similar fashion. Conclusions: Our findings indicate that the retrieved IVIG exerted its lethal effects by blocking the pulmonary circulation without markedly altering the coagulation cascade or immunological events.